Analisis Penyerapan Tenaga Kerja pada Sektor Pariwisata (Sektor Perdagangan, Hotel dan Restoran) Di Kabupaten Badung - Safira Devi Rachmania; Niniek Imaningsih; Riko Setya Wijaya (Universitas Batanghari Jambi, 2021)
The purpose of this research to prove the existence of the influence of the number of foreign tourists visit, the number of domestic tourists visit, hotel occupancy rate, the minimum wage and inflation on employment in the tourism sector in Badung Regency. This research used secondary data or time series for 16 years namely the period 2004-2019. The data analysis technique used is multiple linear regression analysis using spss 16.0. Based on the results of the analysis show that the number of foreign tourist visits, the number of domestic tourist visit, hotel occupancy rates, the minimum wage and inflation simultaneously have a significant positive effect on employment. Partially the number of foreign tourist visits and the minimum wage affect employment in the tourism sector, hotel occupancy rates has negative and significant effect on employment while the number of domestic tourists visit and inflation does not affect employment in the tourism sector in Badung Regency. Variations in the number of foreign tourists visit, the number of domestic tourists visit, hotel occupancy rate, the minimum wage and inflation can explain variations in employment in the tourism sector by 95 percent and by 5 percent explained by other variables outside of this study.